ANALISA AKTIVITAS PENGANGKATAN DENGAN METODE RECOMMENDED WEIGHT LIMIT (RWL) - Ratna Ayu Ratriwardhani (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2019)
Manual material handling if done inappropriately can pose a risk of injury to the body, mainly in the spine, which is usually referred as musculoskeletal disorders (MSDs). Based on direct interview with warehouse workers of PT. X, it is known that in the lifting or transfering mineral water activity often causes pain in the waist and spine. This study is intended to analyze the work posture and the load level that is safe for workers to reduce the risk of MSDs, the analysis is carried out with the Recommended Weight Limit (RWL) method. From the calculation gained RWL origin = 15.36kg / 34.07lbs and destination RWL = 18.54kg / 41.12lbs. Then the origin LI value = 0.9 and destination LI = 0.8. From the results of the Lifting Index can be concluded that the risk level of this work is low and there is no problem with the lifting work. The weight of load raised does not exceed the recommended lifting limit, so there are no repairs to the work needed, but the activity must keep to get attention so the LI value can be maintained and the activity does not bear the risk of spinal injury.